A study of ultrasound-guided perineural injection of the caudal cervical spinal nerve roots in equine cadavers. (July 2021) - Cruz-Sanabria, Jonuel A.; Gaschen, Lorrie; Bragulla, Hermann H.; Mitchell, Mark; Leise, Britta S.
Abstract: Objectives: To develop an ultrasound-guided cervical perineural injection technique for horses and to evaluate and compare the distribution of contrast agent among perineural, intra-articular and periarticular injections. Study design: Prospective, experimental cadaveric study. Animals: A total of 14 equine cadaveric necks. Methods: Bilateral ultrasound-guided perineural injection technique for the caudal cervical spinal nerve roots (CSNRs 5–7) was developed. Paramagnetic or iodinated contrast was injected and the distribution of contrast was evaluated using magnetic resonance (MR) or computed tomography (CT) imaging, respectively. The presence of contrast in the CSNR region was determined by an observer unaware of the technique used for each injection performed. The ability of the perineural injection technique to distribute contrast agent to the CSNR region was compared with intra-articular and periarticular injection techniques. Results: Perineural injection delivered contrast agent to the CSNR region 100% of the time and was significantly different when compared with intra-articular injection ( p  = 0.008). There was no difference in ability to deliver contrast agent to the CSNR region between the perineural and periarticular injection techniques or between the intra-articular and periarticular injection techniques. Conclusion and clinical relevance: The ultrasound-guided perineural injection technique developed in this study accurately delivered contrast agent to the CSNR region in equine cadavers. This technique could potentially be used for the diagnosis and treatment of cervical pain in horses, particularly in cases where intra-articular cervical articular process joint injections have not been beneficial. Further studies are necessary to assess the effectiveness of the ultrasound-guided perineural injection technique in live horses.